Mariano Azuela e a Revolução Mexicana: narrativas entre o desencanto e a esperança - Warley Alves Gomes (2013)
This work aims to analyse Mariano Azuelas intellectual life, one of the most recognized Mexican writers of the 20th century. The analysis is focused on early 1910 decade when Mexican Revolution started until 1952, when Mariano Azuela passed away. Through Mariano Azuelas intellectual life, politics and culture of Mexico are reflected, mainly liaisons between Azuelas novels and the creation of such a thing as a new revolutionary culture, and liaisons between other intellectuals and State at Mexico as well. Also, the changes which ones Mexico went through on the first fifty years of the 20th century are analysed on this work, specially Azuelas view about them.